The influence of absent crowds on National Rugby League match player statistics and running metrics. (May 2022) - Fazackerley, Lewis A.; Gorman, Adam D.; Minett, Geoffrey M.; Caia, Johnpaul; Kelly, Vincent G.
Abstract: Many elite sporting codes have imposed severe restrictions on crowd attendance at games to minimise COVID-19 infection risk, which created a rare opportunity to examine the influence of absent crowds on elite sporting performance. This study used a retrospective observational design to investigate the influence of the crowd in the National Rugby League (NRL) by comparing player statistics and Global Positioning System (GPS) metrics between Round 1 (crowds) and Round 2 (no crowd). Data were obtained for 203 professional NRL players. A linear mixed model with a random intercept (Player ID) was used to assess the relationship between crowd removal and match location on performance indicators and GPS metrics. Effect sizes (ES) were also calculated to determine the magnitude of change. The effect of a crowd and match location were trivial to small (ES range: 0.213 to 0.224). Without crowds, performance indicators relating to decoys (p = 0.022), post-contact metres (p = 0.020), tackle breaks (p = 0.035) and missed tackles increased (p = 0.018), whereas supports decreased (p = 0.005). Without crowds, GPS metrics maximal velocity increased (p = 0.027), and acceleration load decreased (p < 0.001). In away games, relative high-speed running increased (p = 0.020). However, it is possible that margin, opponent tactics, and weather could have influenced changes. The findings suggest that NRL players' performance appears unlikely to be affected by the presence or absence of a crowd. Highlights: This study aimed to examine the effects of crowd removal, due to the COVID-19 pandemic, on professional NRL footballer performance. The crowd's presence/absence had minimal influence on attacking and defending performance indicators. The presence/absence of the crowd had a trivial to small influence on GPS running metrics. Any changes were more likely to result from the score margin and other contextual factors. The removal of the crowd may have reduced the home-ground advantage. However, it appears that elite rugby athletes can maintain optimal performance without a crowd.